Sensitivity of midturbinate versus nasopharyngeal swabs for the detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). (18th August 2021) - Jamal, Alainna J.; Mozafarihashjin, Mohammad; Coomes, Eric; Anceva-Sami, Sofia; Barati, Shiva; Crowl, Gloria; Faheem, Amna; Farooqi, Lubna; Kandel, Christopher E.; Khan, Saman; Li, Angel X.; Mistry, Henna; et al.
Abstract: To compare sensitivity of specimens for COVID-19 diagnosis, we tested 151 nasopharyngeal/midturbinate swab pairs from 117 COVID-19 inpatients using reverse-transcriptase polymerase chain reaction (RT-PCR). Sensitivity was 94% for nasopharyngeal and 75% for midturbinate swabs ( P = .0001). In 88 nasopharyngeal/midturbinate pairs with matched saliva, sensitivity was 86% for nasopharyngeal swabs and 88% for combined midturbinate swabs/saliva.